POLA KOMUNIKASI GURU DENGAN SISWA MELALUI MEDIA EDUKATIF MENDONGENG DALAM MEMBERIKAN PENDIDIKAN AKHLAK (STUDI KASUS SISWA PAUD PELANGI PALMERAH) - Amalliah, Amalliah; Yunita, Ria (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine the Pattern of Communication between Teachers and Students through educative tales in providing moral education. Using a qualitative approach to the theory used is interpersonal communication. This communication pattern that researchers will explore in depth at PAUD Pelangi Palmerah. the results of the study found that children are more interested in learning by using educative media to tell stories, approach to communication patterns using interpersonal communication through effective storytelling media intertwined with effective communication and there is an effect of intertwined communication and also the presence of emotional ties between teachers and Pelangi PAUD students Palmerah in Palmerah Barat I sub-district. This study, concluded the existence of primary interpersonal communication patterns formed between teachers and students. The more often face to face and interaction, through educational media storytelling, the higher the level of interpersonal communication that is formed